Hubungan Daya Tahan Kekuatan Otot Tungkai dengan Laju Lari 100 M pada siswa Kelas VII-3 SMP Negeri 1 Bonepantai - Pateda, Rifka; Mile, Sarjan; Isnanto, Juni (Ideas Publishing, 2024)
In an effort to improve running ability, muscle strength endurance is very important. The aim of this research is to explain the relationship between the strength endurance of body movements, especially the leg or leg muscles, and the extent to which the ability to withstand the strength of the leg or leg muscles affects 100 meter running speed. junior high school students in grades VII–3. In this research, the correlation method is used simultaneously with a quantitative approach. To collect data, a Leg Dynamometer and a Stop Watch were used. Data is analyzed using simple methods and multiple correlations, along with the Product Moment formula. The results showed that (1) there was a significant relationship between leg muscle strength and running speed for 100 meters, with a correlation value of 0.449. The results show that (1) leg muscle endurance influences 100 m running speed because the calculated value is 2.510 > table is 2.008, and (2) variable X influences variable Y. The determination coefficient of 0.201 from this output shows that the influence of the independent variable ( leg muscle endurance) in the dependent variable (100 m running speed) is 20.1% and the significance value is 0.001<0.005